Dampak Kekerasan Dalam Rumah Tangga (KDRT) Terhadap Kesehatan Mental Anak - Iva Nurfaizah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the impact of domestic violence on children's mental health. This study uses a qualitative approach using a descriptive-analytic method. The results and discussion in this study indicate that domestic violence is an act perpetrated by a person against another person which results in physical, sexual and psychological misery or suffering. Domestic violence has an impact on children's mental health, because the family is one of the factors that affect children's mental health. Among the impacts of domestic violence are anxiety, fear, trauma and lack of confidence.